Continued Development of a Data Base Management System Performance Monitor. Volume 2. - Bruner,T D (1984)
This investigation focuses on the problem of analyzing the performance data collected on a Data Base Management System (DBMS). The performance data parameters are categorized and presented to the user using a Data Support System (DSS). The generalized design for a DBMS performance monitor was used to design a user-friendly interface to DBMS performance data. The user interface ot the DBMS performance monitor uses menus to allow the user to select DBMS performance parameter values. The DBMS performance parameter values can also be printed in the form of a performance report. The design was implemented on a VAX 11/780 computer system using the VMS operating system. The TOTAL DBMS was used to collect performance data. The performance values were collected using existing software monitors, job accounting, system error log, an a utility developed at AFIT to collect Data Manipulation Language (DML) response performance data. Originator-supplied keywords included: Data base, Data Base Management System, DBMS, Computer Performance EValuation, Performance Computer Program Documentation, Theses.